Processing Technology of Feed Wafer to Increase Feed Production and Efficiency - Yuli Retnani; N N Barkah; A Saenab; . Taryati (Indonesian Center for Animal Research and Development, 2020)
Feed is one of the important factor that affect livestock productivity, so the availability of good quality feed is a requirement for livestock development in an area. In the tropical area, providing forage as a crucial feed for ruminants was hampered by fluctuating seasons. Likewise, the availability of agricultural waste as an alternative source of feed material experiences the same constraints, easily damaged, and bulky (voluminous). Therefore, feed processing technology is needed so that it is become durable, easily stored, and easily provided for livestock. One way to overcome this is to utilize technology for making wafers. Information regarding technology for making animal feed wafers in Indonesia is still limited. This paper reviews a number of studies that discuss the development of wafer processing technology, types of wafers, the main components of wafer compilers, wafer manufacturing processes, reactions that occur during wafer manufacturing, nutrient quality of various wafers, and the results of research on the use of wafers for feed livestock. Wafers are feeds that are processed using heat and pressure, so that a solid, compact, and high density product is formed. Feed wafer technology is a modification of cube and block feed. Wafers are divided into feed wafers, feed supplement wafers, and complete feed wafers. Feed wafers can be used instead of concentrates. Feed supplement wafers are high in energy and protein. Complete feed wafers contain energy, protein, fiber, and complete minerals that have been adapted to the daily nutritional needs of livestock. Feed wafer processing technology can be one of the strategies to provide feed with a constant composition of nutrients throughout the season and increase production and feed efficiency.